Choice of Force Field for Proteins Containing Structured and Intrinsically Disordered Regions - Zapletal, Vojtěch; Mládek, Arnošt; Melková, Kateřina; Louša, Petr; Nomilner, Erik; Jaseňáková, Zuzana; Kubáň, Vojtěch; Makovická, Markéta; Laníková, Alice; Žídek, Lukáš; Hritz, Jozef (Biophysical journal, 2020)
Biomolecular force fields optimized for globular proteins fail to properly reproduce properties of intrinsically disordered proteins. In particular, parameters of the water model need to be modified to improve applicability of the force fields to both ordered and disordered proteins. Here, we compared performance of force fields recommended for intrinsically disordered proteins in molecular dynamics simulations of three proteins differing in the content of ordered and disordered regions (two proteins consisting of a well-structured domain and of a disordered region with and without a transient helical motif and one disordered protein containing a region of increased helical propensity). The obtained molecular dynamics trajectories were used to predict measurable parameters, including radii of gyration of the proteins and chemical shifts, residual dipolar couplings, paramagnetic relaxation enhancement, and NMR relaxation data of their individual residues. The predicted quantities were compared with experimental data obtained within this study or published previously. The results showed that the NMR relaxation parameters, rarely used for benchmarking, are particularly sensitive to the choice of force-field parameters, especially those defining the water model. Interestingly, the TIP3P water model, leading to an artificial structural collapse, also resulted in unrealistic relaxation properties. The TIP4P-D water model, combined with three biomolecular force-field parameters for the protein part, significantly improved reliability of the simulations. Additional analysis revealed only one particular force field capable of retaining the transient helical motif observed in NMR experiments. The benchmarking protocol used in our study, being more sensitive to imperfections than the commonly used tests, is well suited to evaluate the performance of newly developed force fields.
Keywords: Reproducibility of Results; voda; Molecular Dynamics Simulation; Protein Conformation; simulace molekulární dynamiky; Intrinsically Disordered Proteins; vnitřně neuspořádané proteiny; konformace proteinů; Water; reprodukovatelnost výsledků